2016
DOI: 10.1098/rspb.2016.1127
|View full text |Cite
|
Sign up to set email alerts
|

At odds with the group: changes in lateralization and escape performance reveal conformity and conflict in fish schools

Abstract: Many vertebrates are known to show behavioural lateralization, whereby they differentially use one side of their body or either of their bilateral organs or limbs. Behavioural lateralization often manifests in a turning bias in fishes, with some individuals showing a left bias and others a right bias. Such biases could be the source of considerable conflict in fish schools given that there may be considerable social pressure to conform to the group to maintain effective group evasion. Here, we show that predat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…It was also surprising that laterality had no influence on survival. A number of studies have found that fish exposed to high risk for 4 days developed a risk‐adverse phenotype (Brown, Gardner, & Braithwaite, ; Chivers et al., ; Ferrari et al., ), which used space more conservatively, were lateralized and in one instance survived better in laboratory mesocosms (Ferrari et al., ). Despite the good range and normal distribution in relative lateralization found in the present study, there was no suggestion that mortality was biased by the levels of lateralization displayed by individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also surprising that laterality had no influence on survival. A number of studies have found that fish exposed to high risk for 4 days developed a risk‐adverse phenotype (Brown, Gardner, & Braithwaite, ; Chivers et al., ; Ferrari et al., ), which used space more conservatively, were lateralized and in one instance survived better in laboratory mesocosms (Ferrari et al., ). Despite the good range and normal distribution in relative lateralization found in the present study, there was no suggestion that mortality was biased by the levels of lateralization displayed by individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For organisms with complex life cycles, important traits linked to fitness include large relative size (Perez & Munch, ), large locomotory structures (Langerhans, ), distracting pigmentation (Lönnstedt, McCormick, & Chivers, ; Stevens, ), high growth rates (Hoey & McCormick, ), turning bias (i.e. lateralization, Chivers et al., ), efficient escape responses when threatened (Dugatkin & Godin, ; McCormick & Allan, ), and being more active or bolder in the face of risk (Fuiman, Meekan, & McCormick, ; May, Page, & Fleming, ; McCormick & Meekan, ). While latency to respond to a predator strike has been found to be important, and though it makes intuitive sense that higher performance in escape kinematics should be important to survival, few studies have expressly examined the mechanics of escape performance related to survival under a direct predation threat (Katzir & Camhi, ; Langerhans, ; Walker, Ghalambor, Griset, McKenney, & Reznick, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of this review, it is a question of whether shorter emergence time is advantageous or not, and that would depend on the potential presence of predators. Indeed, it has been shown that strongly lateralized fish respond to predators more rapidly than do non-lateralized fish [86], and exposing fish to higher levels of predation increases the strength of lateralization, irrespective of whether it is to the left or right side [87].…”
Section: Strength Of Lateralization and Performance In Aquatic Vertebmentioning
confidence: 99%
“…A partial list of these situated influences includes the animal’s immediate and long-term goals, the animal’s current physiological condition (e.g., parasite load, pregnancy, etc. ), predator type, alarm calls from conspecifics, social group size, and the environmental context such as ambient temperature, habitat density, their ability to influence the risk of being preyed upon, and even landscape features such as the amount of grass on the ground (e.g., [13-17]. These factors not only influence which defensive action is executed (as suggested by some taxonomies of defensive behaviors (e.g., as suggested by [2, 4]), but also how any given action is implemented.…”
Section: What Is a Reflex?mentioning
confidence: 99%